Business Dynamics and Productivity Growth in the Netherlands - Daan Freeman; Leon Bettendorf; Gerrit Hugo van Heuvelen; Gerdien Meijerink (Center for Economic Studies and ifo Institute (CESifo), 2024)
This study examines the decline in firm dynamism within the Netherlands, potentially linked to the deceleration of productivity growth. We utilise a rich microdata set covering the period 2006-2016, encompassing nearly all Dutch corporations. This dataset facilitates an evaluation of start-ups' and exiting firms' contributions to Total Factor Productivity (TFP) growth across various industries, employing the Melitz and Polanec (2015) decomposition approach. Our findings reveal that in service sectors, the creative destruction hypothesis is substantiated, as start-ups and exiting firms positively impact overall TFP growth. In contrast, TFP growth in manufacturing is primarily driven by incumbent firms. Entry and exit dynamics in this context exert minimal or even negative influence on TFP growth. Although entrants in manufacturing initially display lower productivity than incumbents, their productivity growth outpaces that of incumbents. In services, entrants commence operations with higher initial productivity, a trait that gradually diminishes over time. Generally, entrants with relatively low productivity are predisposed to exit within five years, aligning with the 'up-or-out' pattern.
Keywords: 330; productivity slowdown; firm dynamics; TFP; Netherlands